Possible Histories Arab Americans and the Queer Ecology of Peddling - Karem Albrecht, Charlotte (University of California Press, 2023)
Many Syrians who immigrated to the US beginning in the 1870s worked as peddlers. Traveling enabled men to transgress Syrian norms related to marriage, while Syrian women's roles in peddling led to more economic autonomy. In Possible Histories, Charlotte Karem Albrecht explores this peddling economy to reveal the sexual ideologies imbricated in Arab American racial histories. Possible Histories marshals a queer affective approach to community and family history to show how Syrian immigrant peddlers and their networks of labor and care appeared in interconnected discourses of modernity, sexuality, gender, class, and race. Karem Albrecht theorizes this profession, and its place in Arab American historiography, as a "queer ecology" of laboring practices, intimacies, and knowledge production. This book ultimately proposes a new understanding of the long arm of Arab American history that puts sexuality and gender at the heart of ways of navigating US racial systems. "Possible Histories brings an innovative queer analytic to Arab American history, inquiring into the intimate relationships among itinerant peddlers. Uncovering the role of sexuality in racializing Arab Americans, it challenges respectability politics and brilliantly upends reigning paradigms in Arab American history." - EVELYN ALSULTANY, author of Broken: The Failed Promise of Muslim Inclusion "A deeply personal queer history that is brisk, unsettling, and brimming with insights. Puzzling through gossip, shame, and scandal, Charlotte Karem Albrecht offers an astounding kaleidoscope of Arab Americans in the twentieth century." - NAYAN SHAH, author of Refusal to Eat: A Century of Prison Hunger Strikes "Possible Histories is a rich contribution to queer theorizing on kinship, archives, and diaspora. In this moving tribute to the challenges and traps of recovery work, Karem Albrecht traverses the maze of memory and family with care and thoughtfulness." - JASBIR PUAR, Professor of Women's, Gender, and Sexuality Studies, Rutgers University